Analysis of the conditioning factors of firms clusters genesis (Gestão & Regionalidade, 2017)
This article investigates the evidence about firms' clusters genesis through a systematic literature review. It was possible to identify two main conditioning factors for the genesis of clusters. The first one is characterized by the bottom-up approach, which emerges from entrepreneurial activities. The second one, top-down, refers to the genesis of clusters driven by government actions. The results still point to other conditioning factors for the genesis of clusters: social networks and preexistent organizations; existence of qualified workers; increasing economy; presence of universities and educational institutions; and social division. After the systematic review, it was proposed a model that considers the coexistence of the bottom-up and top-down approaches. The model contemplates the interaction among government, firms, universities, research centers and other support institutions. The study contributes to the literature by organizing explanations that guide future research and to the practice, by raising possible incentive actions to the formation of clusters.